Late Glacial and Holocene lead XRF core scanning data from Füramoos, Southwestern Germany - Oliver A Kern; Andreas Koutsodendris; Finn Süfke; Marcus Gutjahr; Bertil Mächtle; Jörg Pross (PANGAEA, 2021)
Lead content was analyzed by X-ray fluorescence core scanning (XRF-CS) in samples from the Late Glacial and Holocene (c. 14500 – 200 yrs cal. BP) obtained from an ombrotrophic peat bog at Füramoos (southern Germany). The age-depth-model is based on a total of 14 radiocarbon dates and constrained using BACON.